Dirty Hands, the Scapegoat, and the Collective Responsibility of Religious Communities. (11th November 2018) - Untea, Ionut
Abstract : The article connects the debates surrounding the problem of dirty hands with those regarding collective responsibility, mainly via René Girard's scapegoat mechanism and his view on mimetic violence. By virtue of the distinction between group intentions and individual pre‐reflective intentions, the article will explore the notion that groups are morally responsible for acts accomplished with dirty hands, and whether individual participants in group actions are also responsible. Moreover, the article introduces a reflection on the collective shame of a larger community for what only a small group has done in its name. In a religious framework of thought, both the idea of a limited individual responsibility and that of collective guilt are valuable for furthering the dialogue on religious reconciliation.